Angiotensin receptor-neprilysin inhibitor improves coronary collateral perfusion - Li, Kangbo; Kratzmann, Victoria; Dai, Mengjun; Gatzke, Nora; Rocic, Petra; Bramlage, Peter; Grisk, Olaf; Lubomirov, Lubomir T.; Hoffmeister, Meike; Lauxmann, Martin A.; Ritter, Oliver; Buschmann, Eva; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: We investigated the pleiotropic effect of angiotensin receptor-neprilysin inhibitor (ARNi) on collateral-dependent myocardial perfusion in a rat model of coronary arteriogenesis and performed comprehensive analyses to uncover the underlying molecular mechanisms. Methods: A rat model of coronary arteriogenesis was established by implanting an inflatable occluder on the left anterior descending coronary artery followed by a 7-day repetitive occlusion procedure (ROP). Coronary collateral perfusion was measured by a myocardial particle infusion technique, and the putative ARNi-induced pro-arteriogenic effects were further investigated and compared with an angiotensin-converting enzyme inhibitor (ACEi). Membrane receptors and key enzymes of the natriuretic peptide system (NPS), renin-angiotensin-aldosterone system (RAAS) and kallikrein-kinin-system (KKS) were respectively analyzed by quantitative polymerase chain reaction (qPCR) and immunoblot assay. Furthermore, protein levels of pro-arteriogenic cytokines were measured by enzyme-linked immunosorbent assay, and mitochondrial DNA copy number was assessed by qPCR due to their role in arteriogenesis. Proliferation and migration assays with murine endothelial cells were performed under pharmacological modulation of a neprilysin inhibitor (NEPi), with or without bradykinin receptor antagonists. Results: The in-vivo results showed that ARNi markedly improved coronary collateral perfusion, regulated the gene expression of KKS, and increased the concentrations of relevant pro-arteriogenic cytokines. The in-vitro results demonstrated that NEPi significantly promoted murine endothelial cell proliferation, which was diminished by bradykinin receptor antagonists. Conclusion: ARNi improves coronary collateral perfusion and stimulates coronary arteriogenesis via the bradykinin receptor signaling pathway.